Os Jacobinos Negros: Toussaind l'Ouverture e a revolução de São Domingos de C. L. R. James - Marques, Leonardo (Revista Vernáculo, 2002)
Os Jacobinos Negros: Toussaind l'Ouverture e a revolução de São Domingos de C. L. R. James